STRATEGI PEMASARAN INOVATIF DALAM MENARIK GENERASI MILENIAL SEBAGAI NASABAH BANK - Gilang Ramadhan (Draf Solusi Indonesia, 2024)
The millennial generation presents a significant market segment for the banking industry, with their unique characteristics, preferences, and lifestyles. To attract and retain millennials as customers, banks must adopt innovative marketing strategies that align with their digital-centric approach and desire for convenience. Effective strategies include digitizing banking services through user-friendly mobile apps, leveraging AI for personalized services, offering flexible and accessible financial products, providing efficient and secure payment options, engaging in social media and digital marketing campaigns, and utilizing data analytics to understand customer behavior. By implementing these strategies, banks can enhance their appeal, expand their customer base, build long-term loyalty, and develop products tailored to millennial needs, ensuring their relevance in an evolving digital era.